Oxidative Stress, Glutathione Insufficiency, and Inflammatory Pathways in Type 2 Diabetes Mellitus: Implications for Therapeutic Interventions - John Dawi; Yura Misakyan; Stephen Affa; Samuel Kades; Ananya Narasimhan; Fouad Hajjar; Max Besser; Kevin Tumanyan; Vishwanath Venketaraman (Biomedicines)
Type 2 diabetes mellitus (T2DM) is significantly associated with oxidative stress, resulting from the imbalance between reactive oxygen species (ROS) production and antioxidant defenses. This imbalance contributes to insulin resistance, β-cell dysfunction, and complications in organs like the vasculature and nervous system. Glutathione (GSH), a major antioxidant, is crucial for neutralizing ROS, but GSH levels are notably low in T2DM, exacerbating oxidative stress and inflammation. Elevated interleukin-6 (IL-6) levels further intensify inflammation and oxidative stress, disrupting insulin signaling and worsening complications such as nephropathy, retinopathy, and neuropathy. While lifestyle modifications and antioxidant supplementation are current approaches for managing oxidative stress, their effectiveness in preventing complications remains under study. Recent investigations suggest that GSH and Vitamin D3 supplementation may offer dual-action benefits, as Vitamin D3 not only has anti-inflammatory properties but also promotes GSH synthesis. This dual action helps mitigate both oxidative stress and inflammation, addressing key pathological features of T2DM. This review highlights the complex interactions between oxidative stress, GSH insufficiency, and IL-6, and emphasizes the potential of targeted therapies to improve the management and outcomes of T2DM.